The Wahid Institute dan Pluralisme di Indonesia (2004-2008) - Lutfiana, Syifa Ainun; Kurniawati, Kurniawati; Wisnubroto, R; Wulandari, Reni (Universitas Indraprasta PGRI, 2021)
This study discusses the birth and development of The Wahid Institute from 2004 to 2008. The method used in this study is the historical method and the presentation of research results is carried out in the form of descriptive narrative. The results of this thesis study explained that the birth of The Wahid Institute in 2004 was inseparable from Abdurrahman Wahid, Zannuba Ariffah Chafsoh Wahid, Greg Barton, and Ahmad Suaedy who were the initiators of The Wahid Institute. Then there are the founding factors of The Wahid Institute such as social and religious conditions in the post-New Order era, because they were released from the New Order era. because of differences in views, beliefs, culture, and ethnicity. This is due to the lack of pluralism in society, so The Wahid Institute was designed by the initiators to fight for pluralism as expected by Gus Dur.